PERAN KEPEMIMPINAN KEPALA SEKOLAH DAN PROFESIONALITAS GURU DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMA NEGERI 3 PRABUMULIH KOTA PRABUMULIH - DenyTrisna (UNISAN JURNAL, 2024)
This study investigates the role of school principal leadership and teacher professionalism in enhancing student learning outcomes at SMA Negeri 3 Prabumulih, Prabumulih City, Indonesia. The research method employed a combination of qualitative and quantitative approaches. Qualitative methods involved observations, interviews, and document analysis, while quantitative methods utilized questionnaires distributed to students, teachers, and parents. The results indicate that both school principal leadership and teacher professionalism significantly impact student learning outcomes. Visionary leadership and a focus on learning environment by school principals create conducive learning atmospheres, while professional teachers effectively deliver content and provide necessary student support. The synergy between these factors is crucial for enhancing student learning outcomes. The implications of these findings underscore the importance of investing in the development of school principal leadership and teacher professionalism to improve the quality of education at SMA Negeri 3 Prabumulih and other schools. Keywords: School Principal Leadership, Teacher Professionalism, Learning Outcomes